Results of the Cologne Corona surveillance (CoCoS) study: a prospective population-based cohort study$dincidence data and potential underestimation of new SARS-CoV-2 adult infections by health authorities - Oberste-Frielinghaus, Max; Pusch, Lynn-Marie; Roth, Rebecca; Shah-Hosseini, Kija; Schmitz, Jana; Heger, Eva; Dewald, Felix; Müller, Claudia; von Goltzheim, Luise Stach; Lehmann, Clara; Buess, Michael; Wolff, Anna; et al. (BMC public health, 2022)
Current incidence estimates of SARS-CoV-2 in Germany rely to a large extent on case notifications. However, the large number of mild or asymptomatic infections is likely to result in underestimation. Population-based studies can provide valid estimates of the SARS-CoV-2 incidence and thus support health authorities to monitor the epidemiological situation and to initiate, maintain, strengthen or relax effective countermeasures.
Gesehen am 29.11.2022